The Rice Xa3 Gene Confers Resistance to Xanthomonas oryzae pv. oryzae in the Model Rice Kitaake Genetic Background - Liu, Furong; Zhang, Weiguo; Schwessinger, Benjamin; Wei, Tong; Ruan, Deling; Ronald, Pamela (Frontiers in Plant Science, 2020)
The rice XA21 and XA3 pattern receptor kinases, derived from Oryza longistaminata and an Oryza. sativa japonica cultivar Wase Aikoku 3, respectively, confer resistance to strains of the Gram-negative bacterium Xanthomonas oryzae pv. oryzae (Xoo), the causal agent of rice bacterial blight disease. Previously, we showed that transfer of Xa21 to the model rice cultivar Kitaake enhances resistance to Xoo. In this manuscript we demonstrate that Kitaake expressing Xa3 confers resistance to Xoo strain PXO79 and that the stress-related marker genes PR10b and KO5 are upregulated in Xoo-infected Xa3 rice leaves. We also show that rice somatic embryogenesis receptor kinase 2 (OsSERK2) positively regulates XA3-mediated immunity in Kitaake. We found that overexpression of XA21 binding protein 15 (XB15) and XB24, two negative regulators of XA21-mediated immunity, do not affect XA3-mediated immunity in the Kitaake genetic background. Our results indicate that the rice immune receptors XA21 and XA3 employ both shared and distinct signaling components in their response to Xoo. The results are important to further understand pathogen-associated molecular pattern (PAMP)-triggered immunity in rice. Furthermore, the presence of Kitaake rice carrying Xa3 will facilitate genetic research to study the XA3-mediated immunity.